Treatment of acidic raw water using limestone - Mokhtar, Nadiah (2006)
Sg. River is the only raw water source for Yong Peng 2 and 3 treatment plants which supply treated water for domestic, institutional, commercial and industrial use in Batu Pahat. Between the months of January to May 2005, Sg. Bekok registered a low pH of between 2.89 – 3.06. The acidic water hence, escalated the cost for water treatment in Yong Peng. (Southern Water Corporation Sdn. Bhd., 1999). In several extreme cases, the plants were incapable to supply sufficient water to the consumers in Batu Pahat area. The present study attempts to investigate the viability of limestone in treating acidic raw water with high concentration of iron and manganese. Sample of water was collected from tributary of Parit Ngamarto, Bekok Intake and Semberong Lagoon. A lab-scale study using plug-flow reactor system that consists of four limestone-drains was used to treat the raw water. The pH reading was monitored at inflow, outflow and three intermediate points within limestone reactor while effluent was collected for Fe and Mn analysis. Parit Ngamarto, Bekok Intake and Semberong Lagoon raw water sample was recorded an initial pH of 2.5, 2.89 and 3.12 with acidity of 530 mg/L as CaCO3, 75 mg/L as CaCO3 and 51mg/L as CaCO3, respectively. The pH rise gradually as the water flow through limestone-drain at different flow rates (88 mL/min, 42 mL/min and 21 mL/min). The rate of pH rise varies depending on the acidity of the water. The rise of pH was also affected by the amount of limestone used. As pH increased, Fe and Mn concentration was found to decrease. By using statistical analysis i.e Analysis of Variance (ANOVA), a significant increase in pH could be related to the quantity of the limestone used, acidity and flow rate (contact time).